Artistic traditions in the Karakalpak literature of the 19th century - Tokymbetova Gulbahar Abatbaevna (International Journal on Orange Technologies, 2021)
The article deals with the individual peculiarities of the works of the great poet Berdakh. The author of the article discovers some special features pointing out to Berdakh’s originality, and tries to explain them with the help of texts from his works